3x-1=0; 2x+7=5; 3x-x+5x=2,1; x=1,2x-3,6x=-7; 3y-11=1-2y; 2(y+2)= -3(y-1); 4(x-+9)=1; 2x-3(4-x)=5-(x-1)

камил486 камил486    3   06.09.2019 14:20    0

Ответы
alikakusai35 alikakusai35  06.10.2020 21:20
-3x-1=0 (умножаем на -1)
3x+1=0
3x=-1
x=-1/3

2x+7=5
2x=5-7
2x=-2
x=-1

3x-x+5x=2.1
7x=2.1
x=2.1:7
x=0.3

3y-11=1-2y
5y=12
y=12/5

2(y+2)=-3(y-1)
2y+4=-3y+3
5y=-1
y=-1/5

4(x-5)-(7x+9)=1
4x-20-7x-9=1
-3x=30
x=-10

2x-3(4-x)=5-(x-1)
2x-12+3x=5-x+1
6x=18
x=3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра